Regulatory guidelines for medical devices in India: An overview - Radhadevi, Nadimpalli; Balamuralidhara, Veeranna; Kumar, Teggina Math Pramod; Ravi, Valluru (Asian Journal of Pharmaceutics (AJP), 2014)
The objective of the present study offers an overview of regulatory guidelines for medical devices in India. Medical devices are now a pervasive part of modern medical care. They are in many cases associated with quality of care. In some cases, the use of devices has certainly improved quality. In other cases, devices have been associated with many problems. The approach to quality of devices has depended largely on regulation. Recently introduced guidelines and the amendment in the law will provide adequate guidance for both the manufacturers and competent authorities to manage cases efficiently and appropriately. While these regulations and reforms promise to clarify, unify, and expedite the process of manufacturing and importing medical devices into India, they also pose their own challenges and complications. Understanding the regulatory reforms imminent in India will be crucial for foreign companies looking to enter or expand their business in India’s medical markets. It is hoped that the guidelines are implemented and regulated properly with effective outcome.This article highlights current regulations pertaining to applications for medical device registration certificates, medical device clinical trials, and medical device manufacturing/importation licenses.